2021
DOI: 10.2147/idr.s317665
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Physicians About Rational Antibiotic Use and Antimicrobial Resistance Before and After Graduation: A Cross-Sectional Study Conducted in Malatya Province in Turkey

Abstract: Background:We aimed to evaluate the level of theoretical knowledge of rational antibiotic use and awareness about emergence of multidrug resistance (MDR) among the senior students at a medical school and the actively-working family physicians. Methods: This cross-sectional research was carried out between 1 February and 30 April 2019 in Malatya province. Two-hundred twenty-five senior students in the Inonu University Medical School (Group 1) and 230 actively-working family physicians in Malatya primary health … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Similarly, in this study, 26.6% of the physicians indicated that they agree to prescribe antibiotics when asked by the patients because, otherwise, they would have an argument with them. 29 Informing patients about the development of resistance by emphasizing effective management of symptoms without the use of antibiotics, and by making use of public campaigns, patient education materials and brochures will reduce patient expectations and prevent irrational antibiotic prescribing. 30,31 The studies conducted in Turkey have emphasized that since it has been discovered that patients use antibiotic drugs without a doctor's advice, there is a need for training in the rational use of antibiotics in the society and that the media should also play an important role in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in this study, 26.6% of the physicians indicated that they agree to prescribe antibiotics when asked by the patients because, otherwise, they would have an argument with them. 29 Informing patients about the development of resistance by emphasizing effective management of symptoms without the use of antibiotics, and by making use of public campaigns, patient education materials and brochures will reduce patient expectations and prevent irrational antibiotic prescribing. 30,31 The studies conducted in Turkey have emphasized that since it has been discovered that patients use antibiotic drugs without a doctor's advice, there is a need for training in the rational use of antibiotics in the society and that the media should also play an important role in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…34 Some other studies have also reported that providing sustainable education programs for physicians on rational antibiotic use after graduation may contribute positively to reducing antimicrobial resistance rates, increasing awareness, and the RUA. 29 The Turkish Ministry of Health found that antibiotics were included in 34.94% of family physicians' prescriptions in 2011. As a result of the rational antibiotic use programs and trainings provided by the Ministry of Health the rate of antibiotic prescription by family physicians decreased to 24.55 % in 2018, the rate of antibiotic prescription by family physicians found 23.87% in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial effect of the plant extract was evaluated using the disk inhibition zone method. The Kirby and Bauer method [22] was used where the Muller-Hinton agar medium was inoculated with freshly prepared cells of bacteria to yield a growth. After solidification of the agar, a number of sterile disks were dipped into the extract solution and placed on plates.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…There is still a need for ongoing education for physicians on current developments in antibiotic use. 13 …”
Section: Antibiotic Use and Amrmentioning
confidence: 99%